Pengaruh Penggunaan GIS terhadap Kemampuan Analisis Spasial Siswa SMA di Payakumbuh - Ramadhani, Tiara Suci; Bakri, Zamhar; Khairani, Majidah (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2025)
This study investigates the extent to which the use of Geographic Information Systems (GIS) influences students' spatial analysis skills, employing a quantitative approach through a quasi-experimental design. The study population comprised all 11th-grade students at public high schools in Payakumbuh, with the sample drawn purposively from two selected classes. Students in the experimental group received GIS-based instruction, while the control group followed conventional teaching methods. Data were collected using spatial analysis tests, observations, and questionnaires. The data analysis, conducted using a t-test, revealed a statistically significant difference between the experimental and control groups, with a p-value of 0.000, indicating significance at the 0.05 level. The experimental group showed an average score improvement of 19.77 points, compared to only 10.47 points in the control group. These findings suggest that the integration of GIS effectively enhances students' spatial analysis skills, geospatial literacy, and learning motivation. Consequently, incorporating GIS technology into geography instruction holds strong potential to support the implementation of the Merdeka Curriculum through technology-oriented and contextually relevant learning approaches.